EVALUASI KEBIJAKAN TENTANG PENYELENGGARAAN KEBERSIHAN DI KOTA BANJARMASIN - Muhammad Riduansyah Syafari (Universitas Sultan Ageng Tirtayasa, 2015)
The lower performance of the policy on Sanitation Management in Banjarmasin Municipality, since 2000 to 2007, has been basic reason for the importance of evaluation on the by law implementation. The present research on evaluation aims to identify the effectiveness of implemented 2000 by law Number 4 on sanitation management in Banjarmasin Municipality, involving: first, to identify the expected and realized output of policy; second, expected and realized outcome of policy; thirdly, the condition of sanitation after the policy. Descriptive qualitative approach was used in this research through the use of formal evaluation. Results indicated that the implementation of policy Sanitation Management, from 2000 to 2006 was found not effective to realize the clean Banjarmasin Municipality. Because of less optimal implementation, due to no socialization, less human resources, budget, and facilities and infrastructure, and less involvement of private and civil community (NGO, Village and RT/RW) in managing sanitation. The implementation of by law has started to be effective since 2007 to the present day following optimization of Perda through improved performance of old program and socialization of by law, addition and implementation of new program and the involvement of governance element in the program implementation directly related to the community. The effectiveness of policy is observed from 4 programs that have been successfully achieve their output and outcome, namely the cooperation program on waste management with the third party, orderly waste disposal program, orderly waste disposal transport program and orderly waste processing at the TPAs (waste disposal terminal). Even there are 2 programs that have not successfully achieve output and outcome, i.e. the yustisi (justice) program and retribution collection program for sanitation. Therefore, optimization of implemented by law is quite effective.